Prokaryotic diversity in biodeteriorated wood coming from the Bükkábrány fossil forest. (March 2016) - Nikolouli, Katerina; Pournou, Anastasia; McConnachie, Glenn; Tsiamis, George; Mossialos, Dimitris
Abstarct: The oldest standing paleo-forest in the world is located at Bükkábrány in Hungary. Some 7 million years ago a sudden and rapid deposition of sands from a prograding delta resulted in rise of the level of Lake Pannon that covered the landscape. The flood created an anoxic burial environment which preserved unmineralised tree trunks to the present day. Examination of wood sample coming from these trunks using light and scanning electron microscopy revealed extended wood biodeterioration. Culture-independent molecular methods were used to study prokaryotic diversity present in biodeteriorated wood. Phylogenetic analysis of 16S gene clone libraries and 454 pyrosequencing analysis revealed the presence of prokaryotes, including methylotrophic bacteria and bacteria that could be members of the indigenous microbiota found inside the trunk. The rest of identified bacteria are commonly isolated from freshwater habitats possibly reflecting the shift of bacterial biota that occurred in the wood and its close environment after the rise of Lake Pannon. Moreover Archaea were detected in biodeteriorated wood for the first time. The detection of Archaea raises for the first time the question of their possible implication in wood biodeterioration as well as their possible interactions with bacterial communities that colonize wood. Highlights: Wood biodeterioration could be attributed to prokaryotes. Detected bacterial phylotypes could reflect environmental changes. Archaea were detected for the first time in biodeteriorated ancient wood.